(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The objective of the present paper was to prepare different transition metal impregnated heterogeneous catalysts using coal fly ash as a support and to use these catalysts in the wet oxidation of phenol and substituted phenols (2-chlorophenol, 4- chlorophenol, 2.4-dichlorophenol, 2,4,6-trichlorophenol, 2-nitrophenol and 4- nitrophenol). In all the reactions, hydrogen peroxide is to be used as the oxidizing agent and the reactions are to be carried out in a batch reactor under different sets of process variables. The work consisted of (i) preparation of acid and alkali treated fly ash followed by transition metal [Mn(II), Co(II), Ni(II) and Fe(III)] incorporation by impregnation via reflux method, (ii) characterization of the catalysts with spectroscopic and other techniques, (iii) study of the catalytic activity of the materials for wet oxidation of phenol, 2-chlorophenol, 4-chlorophenol, 2.4-dichlorophenol, 2,4,6-trichlorophenol, 2- nitrophenol and 4-nitrophenol using hydrogen peroxide as the oxidizing agent, (iv) optimization of the reaction conditions, (v) monitoring the products as well as Chemical Oxygen Demand of the reaction mixtures for establishing the mechanism of oxidation and (vi) studying the leaching properties of the catalysts with respect to the incorporated metal cations.